Call2Go: A Cross-Platform Strategy Of Kids Online Social Media Influencers - Bouchardet, Cecília C.; Gonçalves, Kênia C.; Passaro, Lucia; Almeida, Jussara M.; Marques-Neto, Humberto T. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16108, 2025)
The presence of children and teenagers (also known as kids) on social media platforms has been increasing steadily recently. Kids influencers, whether children or adults, attract millions of young followers, eager to consume their latest posts, often on multiple platforms such as Instagram and YouTube. While prior work has analyzed kids’ and their influencers’ use of social media platforms, the focus has been mainly on a single platform. Indeed, we are unaware of prior studies investigating how influencers explore their respective profiles on distinct platforms to extend the connection with kids and disseminate content to them. In this paper, we aim to fill this gap by presenting a methodology to build a cross-platform dataset with content produced by a selected set of kids influencers, gathered from two popular social media platforms: Instagram and YouTube.We then use this dataset to identify behavioral similarities and differences of kids influencers exploring their profiles on both platforms. Finally, we point out some evidence of a strategy adopted by these influencers to call their audience’s attention to content posted on another platform. This strategy, referred to as Call2Go, may increase kids’ online permanence, compromising the social development and the health of these young social media users.